Fracture and life - Cotterell, Brian, 1934- (New Jersey : Imperial College Press, 2010)
This book is an interdisciplinary review of the effect of fracture on life, following the development of the understanding of fracture written from a historical perspective. After a short introduction to fracture, the first section of the book covers the effects of fracture on the evolution of the Earth, plants and animals, and man. The second section of the book covers the largely empirical control of fracture from ancient times to the end of the nineteenth century. The final section reviews the development of fracture theory as a discipline and its application during the twentieth century through to the present time
Includes bibliographical references
Keywords: Fracture mechanics; Stone implements